Pengaruh Physical Evidence terhadap Loyalitas Nasabah Bank Syariah: Peran Kepuasan sebagai Variabel Pemediasi - Muhammad Basyir (Jurnal EMT KITA, 2020)
This study analyzes the effect of physical evidence on customer satisfaction and loyalty of sharia banks in Banda Aceh. The sharia banks comprise Bank Aceh Syariah, BRI Syariah, BNI Syariah, Bank Mandiri Syariah, and Bank Danamon Syariah. Data gathering through distributing questionnaires to 250 customers who were determined by purposive sampling. Using multivariate statistical structural equation modeling (SEM) as a data analysis means, the study found that physical evidence has a positive effect on customer satisfaction and loyalty. The existence of customer satisfaction mediates the effect of physical evidence on customer loyalty.